Conversion of concentrated sugar solutions into 5-hydroxymethyl furfural and furfural using Bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Munshi, Mudassir K.; Kelkar, Ashutosh A.; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2015)
Catalytic amounts of recyclable Bronsted acidic ionic liquids (BAILs) yielded HMF (73%) and furfural (81%) with high selectivity from highly concentrated solutions of D-fructose (40 wt%) and D-xylose (3 wt%), respectively. With a 6 wt% D-xylose solution, 73% yield was observed. An activity-property correlation of BAIL is established.